Signatures of electronic phase separation in the Hall effect of anisotropically strained La0.67Ca0.33MnO3 films - Liuqi Yu; Lingfei Wang; Xiaohang Zhang; W B Wu; S von Molnár; Z Fisk; P Xiong (New Journal of Physics, 2013)
Systematic transport measurements have been performed on a series of La _0.67 Ca _0.33 MnO _3 thin films with varying degrees of anisotropic strain. The strain is induced via epitaxial growth on NdGaO _3 (001) substrates and varied by controlling the thermal annealing time. An antiferromagnetic insulating (AFI) state, possibly associated with charge ordering, emerges upon thermal annealing. The Hall effect in these materials exhibits features that are indicative of a percolative phase transition and correlate closely with the emergence of the AFI state. In the paramagnetic phase, the Hall resistivity takes on two slopes in all samples: a decreasing negative slope with increasing temperature at low fields, which is attributed to the carrier hopping motion, and an almost temperature independent positive slope at high fields due to diffusive transport of holes. Significantly, the crossover fields of the Hall resistivity slope at different temperatures correspond to the same magnetization, which is interpreted as the critical point of a magnetic field-driven percolative phase transition. At lower temperatures near the zero-field metal–insulator transition, pronounced enhancement of the Hall coefficient with the development of the AFI state is observed. The enhancement peaks near the magnetic field-driven percolation; its magnitude correlates with the strength of the AFI state and is suppressed with the melting of the AFI state by an in-plane magnetic field. The observations resemble many features of the enhancement of the Hall coefficient in granular metal films near the composition-driven percolation.